Contabilidade digital: uma análise da aceitação da contabillidade digital sobre a percepção dos escritórios de contabildiade de Timon/MA - Silva, Mirely Lorrany Sousa (2022)
With the emergence of digital accounting and major technological advances, accounting has undergone major changes over the years in its methods of performance and demonstrations, in order to provide improvement in services and productivity in accounting offices through automation and use of software. The present study is an analysis of the acceptance of digital accounting on the perception of accounting offices in Timon/MA, with the objective of highlighting the impacts of digital accounting on the way accounting offices operate; Show the level of acceptance and the main difficulties faced for the implementation of digital accounting by accounting offices. In this sense, an exploratory research method was used in its methodology, with an applied research nature, a case study design and a quantitative approach with data collection that took place through a questionnaire and interviews with people who work in accounting offices. Data collection was carried out through a questionnaire applied to professionals registered with the Regional Accounting Council of Maranhão (CRC/MA). In this way, it was verified through its results that digital accounting is essential for the good performance of the accounting service today.